RESPONS PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI (CAPSICUM ANNUUM L.) YANG DIBERI PUPUK ORGANIK CAIR DAUN GAMAL DENGAN DOSIS YANG BERBEDA - WA ODE IRI; ANDI NURMAS; NORMA ARIF; LA ODE MUH. HARJONI; MIRZA ARSIATY ARSYAD; ABDUL MADIKI (Fakultas Pertanian Universitas Halu Oleo, 2023)
This study aims to determine the level of treatment with liquid organic fertilizer on gamal leaves which gives the best effect on the growth and production of chili (Capsicum Annuum L) plants. This research was carried out at the Field Laboratory of Experimental Gardens II, Faculty of Agriculture, Halu Oleo University, Kendari. The study took place from December 2021 to February 2022. This study used a Randomized Block Design (RAK) which consisted of 5 levels of treatment, namely P0: No POC of gamal leaves; P1: POC of gamal leaves 200 ml L-1 tan water-1; P2: POC of gamal leaves 400 ml L-1 tan-1; P3 : POC of gamal leaves 600 ml L-1 tan-1; P4 : POC of gamal leaf 800 ml L-1 tan-1. Each treatment was repeated 4 times as a group so that 20 polybags were obtained. Each treatment used 3 polybags, overall using 60 polybags. The variables observed included plant height, number of leaves, stem diameter, leaf area. number of days of flowering and number of fruit. The results showed that there was an effect on the application of liquid organic fertilizer with Gamal leaves on liquid organic fertilizer of Gamal leaves gave the best effect on growth and production of large chili plants. P3: POC of gamal leaves 600 ml L-1 tan water-1.